1980
DOI: 10.1111/j.1432-1033.1980.tb04295.x
|View full text |Cite
|
Sign up to set email alerts
|

The Energy‐Dependent Degradation of Guanosine 5′‐Diphosphate 3′‐Diphosphate in Escherichia coli

Abstract: Different inhibitors of the energy metabolism have been assayed in Escherichia coli K12 for their ability to increase the level of guanosine 5'-diphosphate 3'-diphosphate (ppGpp) as a consequence of a restriction of its degradation. Inhibitors of the respiration and uncouplers of oxidative phosphorylations had effects similar to carbon-source-induced downshifts while the ATPase inhibitor dicyclohexylcarbodiimide was less efficient. The effects of dicyclohexylcarbodiimide and of the uncoupler carbonylcyanide p-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…We can only speculate about the structure of the induced pore. Tetu et al (1980) have confirmed that the half life of ppGpp is increased 10 times when the protonmotive force is dissipated. These structures have, however, only been observed at much higher peptide to lipid molar ratios than used in this study.…”
Section: Discussionsupporting
confidence: 52%
“…We can only speculate about the structure of the induced pore. Tetu et al (1980) have confirmed that the half life of ppGpp is increased 10 times when the protonmotive force is dissipated. These structures have, however, only been observed at much higher peptide to lipid molar ratios than used in this study.…”
Section: Discussionsupporting
confidence: 52%
“…Despite the fact Wells et al (55) used acidic pH stress to induce the stringent response in H. pylori, they observed the same accumulation pattern for only ppGpp and not the precursor pppGpp, as we showed with alkaline stress in P. aeruginosa. The mechanism triggering the accumulation of ppGpp in response to pH stress might be linked to the pH-dependent perturbation of the proton gradient since treatment with the protonophor carbonyl cyanide m-chlorophenylhydrazone has also been shown to induce a SpoT-regulated stringent response by a reduction of the rate of ppGpp degradation in E. coli (50). Nevertheless, the capability of SpoT to detect and respond to a variety of apparently unrelated stress factors remains a highly complex and greatly unsolved network, which now can be additionally linked to environmental alkaline pH.…”
Section: Vol 190 2008mentioning
confidence: 99%
“…The second regulatory mechanism of the strin-gent response controls the balance between the synthetase and hydrolase activity of ppGpp by SpoT (8,59). In contrast to RelA, SpoT-controlled ppGpp accumulation is triggered by a variety of stimuli, e.g., inhibition of fatty acid metabolism (19,45), carbon deprivation (59), or membrane-perturbating agents (50).…”
mentioning
confidence: 99%
“…In addition to detecting SpoT in high-speed pellets, we also found that the low-speed pellet (30,000 ϫ g) of crude extracts also contained substantial amounts of the SpoT protein. Lowspeed pellets consist primarily of crude membranes, and the localization of SpoT to this fraction could indicate membrane association, as suggested previously (29,30). To determine if SpoT is membrane associated, we fractionated crude membranes as described by Osborn and Munson (20).…”
mentioning
confidence: 99%
“…Carbon source starvation was also shown to result in inhibition of SpoT-mediated (p)ppGppase and thereby account for (p)ppGpp accumulation under these conditions (16). In addition, (p)ppGppase activity is inhibited in vivo by osmotic shock (8), fatty acid synthesis inhibition (26), oxidative phosphorylation uncouplers (30), or long-chain alcohols (19). These effects can be dissociated from the effects of ATP levels (30), leading to the suggestion that the (p)ppGppase activity of SpoT is sensitive to membrane integrity in a manner that might involve membrane association of SpoT (29,30).…”
mentioning
confidence: 99%